Starting an online business for dummies - Holden, Greg (Wiley, 2010)
Armed with a computer, an Internet connection, and a good idea-- but hesitant to take that first step toward making money online? This guide give you confidence by providing you with essential advice and up-to-date trends in e-commerce, all aimed at helping you make money online
Includes bibliographical references and index
Introduction -- pt. I: Launching your online business -- 1. What's new: the latest tools and strategies for your online business -- 2. Opening your own online business in ten easy steps -- 3. Choosing and equipping your new e-business -- 4. Selecting your e-commerce host and design tools --
pt. II: Establishing and organizing your online business -- 5. Organizing your business presence and attracting customers -- 6. Making shipping easy on your e-commerce site -- 7. Accepting payments -- 8. Providing customer service with a virtual smile -- 9. Sourcing worldwide for your business --
pt. III: Building traffic through social networking and more -- 10. Advertising and publicity: the basics -- 11. Search engine optimization -- 12. Selling on Craigslist, Amazon.com, and CafePress --
pt. IV: Expanding beyond your own web site -- 13. Running a business with online auctions -- 14. Taking advantage of Google's tools -- 15. Spreading the word on Facebook, Twitter, and blogs --
Keywords: Electronic commerce; New business enterprises / Computer networks; New business enterprises; Web site development; CD-ROM; Internet; Unternehmensgründung